INFLUENCE OF CARBOHYDRATE GEL “ENERGEL. ENDURANCE” ON SPORTSMEN’S WORKABILITY - Vdovenko, N.V.; Maidanuyk, E.V.; Ivanova, A.M.; Hrobatenko, A.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2017)
Purpose: to study influence of carbohydrate course application on qualified sportsmen’s special workability. Material: workability of cyclic kinds of sports sportsmen (n=14) was determined before and after gel course application under increasing loads. Results: confident increase of work power was found at threshold of anaerobic metabolism (by 12%). Besides, rising of mechanic effectiveness and economy of muscular work at threshold of anaerobic metabolism and at maximal oxygen consumption was registered. Such results witness about presence of conditions for improvement of muscular energy supply at the account o aerobic component that permits to prolong working time without fatigue. Conclusions: purposefulness of carbohydrate gel application in conditions of physical loads, requiring endurance, has been proved. Its application in sportsmen’s training is recommended for increase of training and competition effectiveness.